At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve just isolate y from 2x-y=-1 to get y=2x+1. Then substitute y=2x+1 into 3x-2y=1. So it should be this: 3x-2(2x+1)=1. Distribute to get 3x+4x-2=1. Add the x's to get 7x-2=1, add two to both sides to get 7x=3 and divide to finally get x=3/7.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.